Digital assessment of muscle adaptation in obese patients with osteoarthritis: Insights from surface electromyography (sEMG) - Xinran Luo; Qiaojie Wang; Hongyu Tan; Wenbo Zhao; Yifei Yao; Shengdi Lu (Digital Health)
Background Obesity and severe knee osteoarthritis (KOA) lead to significant gait and muscle adaptations. However, the relationship between core muscle strength and the severity of KOA in obese patients remains unclear. This study aimed to determine the association between muscle strength adaptation and the severity of KOA in obese individuals. Methods We recruited 119 obese participants with unilateral KOA from January 2021 to December 2023, all classified with mild to moderate KOA grades. KOA severity was assessed using the Western Ontario and McMaster University Osteoarthritis Index (WOMAC), which categorized participants into two groups based on disease severity. Electromyographic data from the psoas, gluteus medius, vastus lateralis, vastus medialis, rectus femoris, medial gastrocnemius, lateral gastrocnemius, tibialis anterior, and biceps femoris muscles were collected during isometric and dynamic knee extension. Results Significant differences were observed in all selected muscles between the affected knee joint and the contralateral side during both dynamic and isometric knee extensions. The difference in electromyographic data—including mean absolute value (MAV), root mean square (RMS), and center frequency (CF)—was significantly different across groups categorized by KOA severity. Notably, the MAV values of the vastus medialis, lateral gastrocnemius, and biceps femoris, as well as the CF values of the medial and lateral gastrocnemius, showed no significant differences in some instances during both dynamic and isometric extensions. Conclusion This study indicates that obese individuals with KOA exhibit lower muscle intensity and higher fatigability in comparison to the contralateral side during both isometric and dynamic knee extensions. Furthermore, significant reductions in muscle intensity were observed in the psoas, gluteus medius, vastus lateralis, rectus femoris, medial gastrocnemius, and tibialis anterior muscles, correlating with the advanced severity of KOA.